2022
DOI: 10.1080/07853890.2022.2124449
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in response to non-small cell lung cancer immunotherapy: an updated meta-analysis

Abstract: Background Studying sex differences in the efficacy of immunotherapy may contribute to the practice of the precision medicine, especially in non-small cell lung cancer (NSCLC), a kind of cancer with sexual bimorphism. Methods Published randomized controlled trials (RCTs), published by PubMed, Medline, Embase, and Scopus, before 15 June 2022, testing immunotherapy (CTLA-4 or PD-1/L1 inhibitor alone, combination or with chemotherapy) versus non-immunotherapy (receiving ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…In the NSCLC cohort of another meta-analysis carried out by Grassadonia et al, PFS was higher in immunotherapy-treated males than in females, and anti-CTLA-4 treatment was associated with longer OS in males [ 117 ]. Similar results were also observed Laing et al in a more recent meta-analysis [ 118 ]. In contrast, a meta-analysis carried out by Conforti et al showed longer OS in women than in men treated with ICBs; however, this study excluded a large number of female patients from their final analysis, making interpretation of the results difficult [ 119 ].…”
Section: Differences In Response To Therapysupporting
confidence: 90%
“…In the NSCLC cohort of another meta-analysis carried out by Grassadonia et al, PFS was higher in immunotherapy-treated males than in females, and anti-CTLA-4 treatment was associated with longer OS in males [ 117 ]. Similar results were also observed Laing et al in a more recent meta-analysis [ 118 ]. In contrast, a meta-analysis carried out by Conforti et al showed longer OS in women than in men treated with ICBs; however, this study excluded a large number of female patients from their final analysis, making interpretation of the results difficult [ 119 ].…”
Section: Differences In Response To Therapysupporting
confidence: 90%
“…21 More recently, several update meta-analyses also reported that female patients had a greater treatment outcomes improvement than male patients. [22][23][24] Consistently, this study analyzed 175 patients with untreated advanced or metastatic NSCLC received PD-1 blockade plus chemotherapy or chemotherapy and also observed that female patients derived a larger benefit from first-line PD-1 blockade in combination with chemotherapy, but not chemotherapy, than male patients. Taken together, these findings suggest that female patients with untreated advanced or metastatic NSCLC could derive a larger benefit from PD-1 blockade plus chemotherapy.…”
Section: Discussionmentioning
confidence: 62%
“…Otherwise, women experienced increased survival rates, in chemoimmunotherapy ( 34 ). Additionally, the pooled HRs comparing ICIs vs chemotherapy were 0.74 (95% CI0.67-0.81) for men and 0.83 (95% CI 0.73-0.95) for women ( 35 ). Better PFS was also observed in advanced NSCLC male patients treated with ICI (5 months vs 4).…”
Section: Sex-related Differences In Response To Pd-1/pd-l1 Blockade I...mentioning
confidence: 99%